Prinsip Distribusi dalam Islam dan Implementasinya dalam Ekonomi Modern: Kajian Literatur - Habibis Salam; Mohd Winario; Muhammad Zakir (EL-EMIR Institute, 2026)
Distribution is one of the fundamental aspects of an economic system that plays an important role in creating justice and social welfare. From the Islamic perspective, wealth distribution is not merely viewed as an economic activity, but also as part of moral and social responsibility based on the values of justice, balance, and public benefit (maslahah). The principles of distribution in Islam emphasize the prohibition of wealth concentration among certain groups, the obligation to share wealth through social instruments such as zakat, infaq, sadaqah, and waqf, as well as the requirement to conduct economic activities ethically. This article aims to examine the principles of distribution in Islam and analyze their implementation in the context of the modern economy. The method used is a literature review of relevant scientific sources, including journals, books, and academic publications. The results of the study indicate that Islamic distribution principles have strong relevance to modern economic challenges, particularly in addressing income inequality and improving social welfare. The implementation of Islamic distribution values in modern economic systems can serve as an alternative solution to creating a more just, inclusive, and sustainable economy.